2016
DOI: 10.3389/fnbeh.2016.00127
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Link between Supra-Second Open-Ended Timing Sensitivity and Obsessive-Compulsive Tendencies

Abstract: One of the main characteristics of obsessive-compulsive disorder (OCD) is the persistent feeling of uncertainty, affecting many domains of actions and feelings. It was recently hypothesized that OCD uncertainty is related to attenuated access to internal states. As supra-second timing is associated with bodily and interoceptive awareness, we examined whether supra-second timing would be associated with OC tendencies. We measured supra-second (~9 s) and sub-second (~450 ms) timing along with control non-tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…Previous studies on time perception have reported that intervals shorter than 1000 ms tend to be automatic processes [49], which do not require significant cognitive resources when participants are familiar with the rhythm. However, as the interval becomes longer, more mental processes [50,51], such as attention and working memory would come into work, occupying additional cognitive resources. Accordingly, this study employed two kinds of time intervals, 1000 ms and 1500 ms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on time perception have reported that intervals shorter than 1000 ms tend to be automatic processes [49], which do not require significant cognitive resources when participants are familiar with the rhythm. However, as the interval becomes longer, more mental processes [50,51], such as attention and working memory would come into work, occupying additional cognitive resources. Accordingly, this study employed two kinds of time intervals, 1000 ms and 1500 ms.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies on cross-domain comparisons focus on processing physical standards of defined durations in the sub-second range (typically up to 1 s, sometimes even up to 2 s) and the supra-second range (typically above a few seconds). These studies indicate a dissociation between these two timescales, suggesting the involvement of different neuronal processes in these two domains which are controlled by different mechanisms (e.g., Lewis and Miall, 2003a , b ; Ulbrich et al, 2007 ; Morillon et al, 2009 ; Bangert et al, 2011 ; Gilaie-Dotan et al, 2011 , 2016 ). Specifically, the sub-second range is assumed to be associated with motor and sensory processes and is known as “automatic timing.” In contrast, the supra-second range, known as “cognitive timing,” is associated more with cognitive mechanisms allowing the perception of accumulating durations.…”
Section: Introductionmentioning
confidence: 93%